Dos novos saberes básicos dos alunos e das novas competências dosprofessores do 1.º Ciclo do Ensino Básico - Silva, Ana Almeida (2010)
The social changes that presently press and challenge the School, namely as to teachers’ roles, functions and performance, imply the need to rethink their training so that they can respond more adequately to emerging challenges. These have to do particularly with new skills that these conditions demand from all citizens and that are understood, from an epistemological point of view, as knowledge to act responsibly. Therefore, and with the aim of deepening these issues, a doctoral study was developed between 2004 and 2008, under the scientific cooperation network “New basic skills for the citizens of the XXI century, new challenges to the training of teachers”. This study, of a qualitative nature, was developed according to approaches specific to complexity and systemics, of which we highlight the principles of totality – in which phenomena are perceived as global and dynamic systems – and of recursiveness, admitting the dialectic relationship between the various subsystems considered. From the methodological point of view and so as to build an integrated perspective of the object under study, a set of specific procedures was used, namely literature review, inquiry through questionnaire and semi-structured interview (mixed-methods). As to the results these can be read according to three axes. In the first, that refers generically to the evolution of students’ basic skills, contributions seem to suggest the need to support the teaching/learning processes not only on the reading, writing and counting skills, but also in the development of other basic skills of a general and transversal nature, such as learning to learn, learning to live with others and learning to do from a problem solving perspective that synthesises learning to be. The second axe has to do with competences required of teachers for the development of those skills perceived as structuring of the processes of development. Data collected in the more extensive phase of the study suggest that the framework of competences of primary teachers should integrate the same dimensions, valuing the competences of critical reflection, learning to learn, and also the development of professional knowledge in its multiple dimensions. The third axe relates to the quality of the ambiances and cultures of teacher education and supervision that facilitate students and teachers’ learning. Generally, data suggest that the environments that foster a dimension of wide-ranging curricular practice, in diversified contexts that value the principles of respect for the person and critical reflection, seem to fit better to the personal and professional development of teachers, within the context of contemporary societies. Globally, it is possible to verify that the axes considered point to a recursive set of skills and competences that, at different levels, imply a compromise with action, from a vision of the world that is compromised with the ideas of common wealth, that is, of universal citizenship.